SUPPLY CHAIN ​​MANAGEMENT PERFORMANCE ANALYSIS USING THE SCOR METHOD AT PT. HATTEN BALI TBK: AN EVALUATION AND OPTIMIZATION STUDY - I Komang Sudiasa; I Wayan Santika (Adisam Publisher, 2025)
Supply Chain Management (SCM) involves the integration and coordination of various activities within the supply chain to enhance operational efficiency and customer satisfaction. This study aims to identify the performance and challenges faced by the company, such as demand fluctuations and delivery delays. The research analyzes SCM performance at PT. Hatten Bali Tbk, an alcoholic beverage distributor, using the Supply Chain Operation Reference (SCOR) model based on the attributes of Reliability, Responsiveness, Cost, and Asset Management through a quantitative descriptive approach. Data were collected through interviews and direct observation. The results show that the POF (Perfect Order Fulfillment) metric reached 96.25%, and the OFCT (Order Fulfillment Cycle Time) metric had an average order fulfillment time of 2 days. However, the COGS (Cost of Goods Sold) was relatively high at 54.47%, and the CTCCT (Cash-to-Cash Cycle Time) reached 106 days, indicating a need for improvement in cost efficiency and asset management. This study enhances the company’s understanding of its SCM performance and provides strategic recommendations to improve efficiency and competitiveness in the market..